Construction of a recombinant baculovirus expressing the hemaglutimin (ha) of an A/H5N1 clade 2.3.3.1b virus - Hoa, Nguyen Thi; Quyen, Dong Van (Academia Journal of Biology, 2015)
Highly pathogenic avian influenza A (H5N1) virus is still a threat to public health, especially, the emergence of a new clade recently with more virulent and resistant to the vaccine developed from the previously circulating clade has raised the need for development of new vaccines. With the ultimate aim of producing influenza virus-like particles (VLPs) vaccine, in this study we created recombinant baculovirus expressing Hemagglutini (HA) from H5N1 virus clade 2.3.2.1b isolated in Quang Ngai province (DkQN37/11) – which is resistant to NIBRG14 (clade 1) currently used in Vietnam. The HA - encoding gene was amplified by PCR with a specific pair of primers, which has Kozak sequence, initation codon and BamHI site at the 5’ of the forward primer and the recognition sequence of HindIII at the 5’ of the reverse primer. The PCR product was cloned into pCR2.1 and sequenced then inserted into the baculovirus vector (pBluBac4.5 / V5-His-TOPO, Invitrogen) at BamHI and HindIII sites to yield pBuBacHA. Vector pBluBacHA then co-transfected with baculovirus DNA into insect cells (Sf9) to generate recombinant baculovirus. The presence of ha gene and the expression of recombinant HA protein in the recombinant virus were detemined by PCR and Western blot using anti-HA antibody. PCR and Western blot results confirmed that we have successfully created a recombinant baculovirus expressing surface antigens of influenza A/H5N1 clade 2.3.2.1b. Our work provides essential material for further study to develop A/H5N1 VLP vaccine in Vietnam.